Rapunzel syndrome in a seven year old female - Gupta, Anand; Kaur, Jaswinder; Wadhwa, Nishant (The Turkish Journal of Pediatrics, 2017)
Rapunzel syndrome is characterized by gastric trichobezoar with extension beyond pylorus. Seven year old female presented with chronic pain abdomen and loss of appetite. Upper gastrointestinal (UGI) endoscopy showed large trichobezoar in the stomach with its tail extending into proximal duodenum. Child underwent exploratory laparotomy and a large trichobezoar measuring 15 cm was removed. Psychiatric opinion revealed that the child was suffering from `trichotillomania`; an obsessive compulsive disorder. UGI endoscopy is the preferred modality for diagnosis, as it delineates the mass and its extent. Small bezoars can be extracted via endoscopy using various disintegrating techniques but large bezoars need surgical management.